The effect of labour unions on payout policies : a cross-country regression analysis - Velten, Leon David (2022)
This paper seeks to study an additional effect on payout policies. In particular, the effect of labour unions on payout polices on a cross-country data sample representing 35 countries, 3,461 firms and 41,504 data points in total is analysed. In contrast to previous research that primarily analysed US American firm samples, this dissertation’s major finding corresponds to a significant positive relationship meaning that an increase in unionization density, the indicator for labour union, leads to an increase in payout ratios. Also, the paper checked whether previous research results from Chino (2016) can be applied to an international context. In particular, he claimed that the effect of unionization on payout policies is heterogenous across firms and depends heavily on profitability. This hypothesis cannot be confirmed due to weak regression results – the corresponding indicator, an interaction term between union density and profitability, is positive but not significant which is why it cannot be assumed that the coefficient is statistically different from zero. As a last measure, the inclusion of further country-specific characteristics, the potential reason for weak results in the first regression models, has not contributed to higher regression accuracy.